2014
DOI: 10.1080/08946566.2013.832605
|View full text |Cite
|
Sign up to set email alerts
|

Informing Evidence-Based Practice: A Review of Research Analyzing Adult Protective Services Data

Abstract: The mission of Adult Protective Services (APS) is to protect older and vulnerable adults from abuse, neglect, and exploitation. The complexity of APS cases and the potential for life-changing interventions point to the need for research that examines and evaluates APS practices. A literature review identified 50 studies published during a 16-year period that used APS agencies, clients, data, or resources to test hypotheses regarding elder abuse. The analysis revealed promising efforts toward knowledge developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 53 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…Risk factors for perpetrators of abuse include substance abuse, mental illness, and criminal history (Ernst et al 2013). Caregivers who struggle with substance abuse more commonly commit physical and emotional forms of abuse (Ernst et al 2013). Additionally, caregiver burden has greater association with neglect than physical abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for perpetrators of abuse include substance abuse, mental illness, and criminal history (Ernst et al 2013). Caregivers who struggle with substance abuse more commonly commit physical and emotional forms of abuse (Ernst et al 2013). Additionally, caregiver burden has greater association with neglect than physical abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Ernst and colleagues (2013) found that elder abuse victims are most often non-white and women with lower SES, and have a greater number of impairments in cognition and activities of daily living (ADLs). Risk factors for perpetrators of abuse include substance abuse, mental illness, and criminal history (Ernst et al 2013). Caregivers who struggle with substance abuse more commonly commit physical and emotional forms of abuse (Ernst et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A major barrier constraining progress in EM intervention research is a lack of tools to measure intervention outcomes (Ernst et al, 2014;Stolee, Hiller, Etkin, & McLeod, 2012). Although EM screening/assessment instruments have been developed to indicate the presence of abuse/neglect (Beach et al, 2017;Gallione et al, 2017), the field lacks tools that measure the extent of case resolution over the course of intervention.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…APS programs respond to over 760,000 EM reports per year (National Adult Protective Services Association [NAPSA], 2012), and evidence would suggest that APS caseloads are rising (U.S. Government Accountability Office, 2011). Despite growing demand for APS, EM victims continue to be exposed to interventions that lack evidence of effectiveness (Ernst et al, 2014).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Studies of prevalence of abuse and neglect have taken place in several countries and are used to evidence the need for political and public commitment to safeguard people at risk and address underlying causation (Pillemer et al 2016). Within this context there are new efforts to obtain data about specific forms of abuse or survivors and about professional interventions (Ernst et al 2013). In England Fyson (2015) has recently been critical of the inadequacies of adult safeguarding data from local authorities, finding that these lead to invalid and unreliable information.…”
Section: Introductionmentioning
confidence: 99%